2017
DOI: 10.1080/09540121.2017.1394964
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use, expectancies and HIV-related sexual risk: a cross-sectional survey of male migrant workers in South India

Abstract: Male migrant workers (MMWs) in India are vulnerable to developing alcohol-related problems and engaging in unprotected sex, putting them at risk of HIV. Research has shown that alcohol-related expectancies mediate vulnerability to alcoholism. We examined which expectancies were associated with sexual risk and drinking. We surveyed 1085 heterosexual MMWs in two South Indian municipalities, assessing expectancies, sex under the influence, and unprotected sex with female sex workers (FSW) and casual female partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In multivariate logistic regression, the expectancy of having more fun helped drive the combination of alcohol and unprotected sex with partners (OR = 1.22, p < 0.05). Men concerned about alcohol-induced deficits were less likely to drink with partners (OR = 0.81, p < 0.01) but more likely to have unprotected sex with them (OR = 1.78, p < 0.01) [65].…”
Section: Alcohol and Nicotine Abusementioning
confidence: 99%
“…In multivariate logistic regression, the expectancy of having more fun helped drive the combination of alcohol and unprotected sex with partners (OR = 1.22, p < 0.05). Men concerned about alcohol-induced deficits were less likely to drink with partners (OR = 0.81, p < 0.01) but more likely to have unprotected sex with them (OR = 1.78, p < 0.01) [65].…”
Section: Alcohol and Nicotine Abusementioning
confidence: 99%
“…Therefore, the transport agencies in the government, healthcare stakeholders, and employers in the trucking industry should work in collaboration to ensure that substance use among the LDTDs is controlled. In India, excessive alcohol use during or before sexual intercourse was found to influence poor condom use [ 19 ]. Other studies have identified alcohol use as likely to influence risky sexual behaviours among the LDTDs during sexual interactions [ 15 , 18 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using an interviewer-administered structured questionnaire developed after a critical review of literature [56][57][58][59]. The questionnaire captured information on socio-demographic characteristics such as sex, age (in years), marital status, highest educational attainment, length of stay in a particular informal settlement, average individual monthly income, history of psychoactive substance use, sexual expectancies and inhibitions.…”
Section: Data Collection and Study Variablesmentioning
confidence: 99%